Development of Non-Player Character with Believable Behavior: a systematic literature review - Silva, Guilherme Alves da; Souza Ribeiro, Marcos Wagner de (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2021: Anais Estendidos do XX Simpósio Brasileiro de Jogos e Entretenimento Digital, 2021)
Non-player character or non-playable character (NPC) does not always have appropriate and responsive behaviors. When the decision-making process is more artificial than intelligent, it can lead to quality issues in a game and even reduce player interest. Based on this statement, this article presents a Systematic Literature Review on the development of NPC with credible behaviors. The review enabled the mapping and knowledge of the current state of the art extracted from 18 related studies. It was found that certain techniques traditionally used by the gaming industry have become a major obstacle in generating more engaged NPC behavior in the virtual environment.